Favorable cardiovascular risk factor profile is associated with lower healthcare expenditure and resource utilization among adults with diabetes mellitus free of established cardiovascular disease: 2012 Medical Expenditure Panel Survey (MEPS). (March 2017) - Feldman, David I.; Valero-Elizondo, Javier; Salami, Joseph A.; Rana, Jamal S.; Ogunmoroti, Oluseye; Osondu, Chukwuemeka U.; Spatz, Erica S.; Virani, Salim S.; Blankstein, Ron; Blaha, Michael J.; Veledar, Emir; Nasir, Khurram
Abstract: Background and aims: Given the prevalence and economic burden of diabetes mellitus (DM), we studied the impact of a favorable cardiovascular risk factor (CRF) profile on healthcare expenditures and resource utilization among individuals without cardiovascular disease (CVD), by DM status. Methods: 25, 317 participants were categorized into 3 mutually-exclusive strata: "Poor", "Average" and "Optimal" CRF profiles (≥4, 2–3, 0–1 CRF, respectively). Two-part econometric models were utilized to study cost data. Results: Mean age was 45 (48% male), with 54% having optimal, 39% average, and 7% poor CRF profiles. Individuals with DM were more likely to have poor CRF profile vs. those without DM (OR 7.7, 95% CI 6.4, 9.2). Individuals with DM/poor CRF profile had a mean annual expenditure of $9, 006, compared to $6, 461 among those with DM/optimal CRF profile ( p < 0.001). Conclusions: A favorable CRF profile is associated with significantly lower healthcare expenditures and utilization in CVD-free individuals across DM status, suggesting that these individuals require aggressive individualized prescriptions targeting lifestyle modifications and therapeutic treatments. Highlights: Those with DM were 8 times more likely to have poor CRF profiles than those without DM. Presence of DM yielded high healthcare expenditure and resource utilization. Improving CRF profile reduced cost independent of DM status. Individuals with DM spent $2774 more than individuals without DM.